Ernst Jünger, total mobilisation and the work of war. (July 2017) - Costea, Bogdan; Amiridis, Kostas
This review article explores three interconnected texts written in the 1920s and 1930s by the German intellectual Ernst Jünger: Copse 125, Total Mobilisation and The Worker. Dominion and Form . They contain his original analyses of the relationship between war, destruction, organisation and technology. Jünger argued that entering the realm of total organisation, that is, organisation which claims its ground to be scientific, calculated, planned, rationally-administered and technological, destruction is subtly appropriated into, and thought of, as a process of production . Jünger understood war as an increasingly 'necessary' and permanent requirement of the politics of peace and freedom. He anticipated the transformation of destruction into a major field of experimentation with, and through, complex state and private organisational networks (civilian, military and corporate), and into a prime arena of scientific, technological and managerial development. He analysed the emergence of new political discourses and systems whose common ground was to invoke permanent insecurity, risks and dangers and claim the need to manage the peaceful existence of liberal societies.